E-module development using Exelearning Web Application on Newton's Law Material for Class X Senior High School - Azhar, Azhar; Nisa, Khairun; Syafi'i, Muhammad (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
This study aims to determine the development of e-modules using an exeleaning application on Newton's law material for class X SMA. This research was carried out in the physics education laboratory for the 2021/2022 academic year. The method used in this research is ADDIE. Where ADDIE consists of Analysis, Design, Development, Implementation and Evaluation. The instrument used in data collection used a validation questionnaire from the validator lecturer, which consisted of 3 validators and was validated 2 times for each lecturer until the e-module validation questionnaire indicator was declared valid. The data collection technique in this research is descriptive analysis, by calculating the validation score for each assessment indicator. The result of the research is the validity value that is already valid with the average value obtained for each indicator above 3.2 where the highest value is 4.3.